Biodiversity support infrastructures: Planning the urban ecosystem (Ciudades, 2017)
Urban areas have an important paper in the conservation of biodiversity, as much by their role supporting a highly specialized ecological community as by their incidence in the global decline of biodiversity. The present article develops several working lines, from ecosystemic perspective, oriented to improve the behavior of the cities respect to biodiversity loss. The main exposition of the work talks about biodiversity support infrastructures, a set of urban elements specifically oriented to improve biodiversity and to solve the problems that traditionally affects the relation between biodiversity and citizens. The paper describes several of these infrastructures, designed so much as isolated elements as in combination with green zones, parks, gardens and with constructed elements and buildings. Also the criteria and conditions necessary to design a program of urban biodiversity are analyzed, focusing on the adaptation to the objectives and necessities of the urban spaces planning. Finally, some of the main programs of biodiversity developed in European cities are superficially described.
Keywords: urban biodiversity; ecological connectivity; greenways; corridors; ecological networks; biodiversity support infrastructures; urban planning; urban landscape